Immunity Indicators of Children Infected with Helminths (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The study comprehensively analyzed the parameters of immunity in case of worm infestations in children. The leukocyte formula of blood and indicators of cellular immunity were studied, represented by subpopulations of CD3+, CD4+, CD8+, CD16+, CD25+, CD95+ apoptosis receptor, indicators of humoral immunity CD20+ and immunoglobulins of the IgA, IgM, IgG, IgE class depending on the type of helminthiasis. A differentiated approach to the distribution of pathogens makes it possible to study the effect of each parasitic agent on the child's immune system separately.